Analisis Pusat Pertumbuhan Dan Wilayah Hinterland Di Kota Samarinda - Asmara, Novyanto Panji; Aprianti, Yesi (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine the sub-district which is the center of growth and the sub-district that is the Hinterland area to the growth center in the city of Samarinda. The research method used in this research is descriptive quantitative method. The type of data from this research is secondary data in 2021 in 10 sub-districts in Samarinda City. The variables used in this study are the number of available educational facilities, health facilities, economic facilities, facilities for places of worship, transportation facilities, population and distance from each sub-district in Samarinda City. This study also accommodates the adequacy of facilities in each sub-district in Samarinda City to see the interaction factors between regions. The analytical tools used in this research are scalogram analysis, centrality index analysis and gravity analysis. The data was processed using Microsoft Excel 2016. The results of this study indicate that the Samarinda Kota, Sungai Pinang and North Samarinda sub-districts are the sub-districts that are the center of growth in Samarinda City. Samarinda Ulu District, Samarinda Ilir District and Sungai Pinang District are hinterland areas that have the highest interaction value with sub-districts that are growth centers in Samarinda City.